Problem Based Learning dan Discovery Learning: Komparasinya terhadap Keterampilan Berpikir Kritis pada Materi Sistem Pernapasan - Ni Komang Ema Karistiawati; Kompyang Selamet; Putri Sarini (PendIPA Journal of Science Education, 2024)
This research aims to analyze the differences in critical thinking skills between students taught using the Problem Based Learning model and students taught using the Discovery Learning model. This research was type of quasi-experimental research, with a Pretest - Posttest Non Equivalent Control Group Design research design. The research sample was obtained from the entire population of class VIII students at SMP Negeri 1 Rendang, totaling 63 students using saturated sampling techniques. Data collection in this research was carried out using the test method. The data collection instrument used was a multiple choice test. The data obtained were analyzed using descriptive analysis techniques and t-test inferential statistical analysis. The results obtained in this research are as follows. (1) The t-test analysis shows the t value is 4,295 and the significance is less than 0.05 so the null hypothesis is rejected. This means that statistically there is a significant difference in critical thinking skills between students taught using the Problem Based Learning model and students taught using the Discovery Learning model. (2) Descriptively, the average critical thinking skills of experimental group I which used the Problem Based Learning model was 81, superior to experimental group II which used the Discovery Learning model with an average of 72. This shows that the evaluated comparison results of the Problem Based Learning model were superior to Discovery Learning model, especially on the Human Respiratory System material.